Periovarian Adipose Tissue - an Impact on Ovarian Functions - Szyrzisko, W; Grzesiak, M (Physiological research, 2024)
Periovarian adipose tissue (POAT) is a type of gonadal white adipose tissue that surrounds the ovary. POAT is a source of various bioactive molecules, such as adipokines, cytokines, chemokines, growth factors and hormones. Thereby it could influence crucial ovarian functions. Recent findings showed that removal of POAT affects folliculogenesis and steroidogenesis in the ovary. Furthermore, changes in the morphology and function of POAT were observed in women during menopause or polycystic ovary syndrome. Although the relationship between the body's energy status and fertility in females is generally well known, the contribution of POAT remains still elusive. Therefore, the objective of this review is summarizing the actual state of knowledge about POAT function in physiological and pathological processes within the ovary.
Keywords: syndrom polycystických ovarií; Humans; Polycystic Ovary Syndrome; lidé; Female; fertilita; tuková tkáň; Fertility; Adipose Tissue; Adipokines; ženské pohlaví; adipokiny